2021
DOI: 10.21512/lc.v15i2.7497
|View full text |Cite
|
Sign up to set email alerts
|

An Ecolinguistic Study on Ecospiritual Tourism of Rebo Buntung Commoddification

Abstract: The research examined the relationship between cultural ritual, linguistic, and ecology in the context of ecotourism. It aimed to encourage, stimulate, and integrate the use of religious tradition’s terms in understanding and reinterpreting the environment and human relations and its roles. Cultural forms and elements basically had the potential to be used as a tourism commodity, meaning that they could be commodified. The research also related to ecolinguistics, a study that discussed language associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The study of foregrounding environment and language is existed in ecospiritual tourism in Rebo Buntung, after observing the location it was found that the action of maintaining ecology spiritual, culture, and language, especially the interrelation positively affects the people's relationship harmony and also the economy level due to the location as tourism site (Supatmiwati et al, 2021). Then the other study due to the language and ecology is on the analysis of vegan pamphlets which campaign the suggestion to stop killing animals.…”
Section: Ecolinguistics and The Previous Related Researchmentioning
confidence: 99%
“…The study of foregrounding environment and language is existed in ecospiritual tourism in Rebo Buntung, after observing the location it was found that the action of maintaining ecology spiritual, culture, and language, especially the interrelation positively affects the people's relationship harmony and also the economy level due to the location as tourism site (Supatmiwati et al, 2021). Then the other study due to the language and ecology is on the analysis of vegan pamphlets which campaign the suggestion to stop killing animals.…”
Section: Ecolinguistics and The Previous Related Researchmentioning
confidence: 99%
“…The term Rebo Bontong, according to the Sasak language, Rebo means Wednesday, while Bontong means the end of the last, hence Rebo Bontong means the last Wednesday in the month of Safar. The purpose of the ceremony is to eliminate disasters (Supatmiwati et al, 2021).…”
Section: Introductionmentioning
confidence: 99%